Comparative Evaluation of Ropivacaine versus Levobupivacaine for Postoperative Epidural Analgesia in Geriatric Patients Posted for Orthopedic Surgeries - Shilpi Misra; Furkan Akhtar Ansari (Academia Anesthesiologica International, 2020)
Background: With increasing life expectancy, improved healthcare and increasing prosperity, the proportion of elderly population is increasing throughout the world. Post-operative pain management among elderly patients  is a challenging and daunting task for anaesthesiologists. Altered redistribution kinetics as well as compromised drug clearance capacity render geriatric patients particularly vulnerable to drug-induced complications. Regional anaesthesia is preferred for the older patients because this form of anaesthesia causes the least interference with the metabolic functions.Subjects and Methods:56 elderly patients  scheduled for elective orthopaedic lower limb surgery under epidural anaesthesia with continuous post-operative epidural analgesia were enrolled in this prospective randomised study and were randomly allocated to two groups  consisting 28 patients each as under: Group I : Epidural analgesia Ropivacaine 0.2% @ 6ml/hr. Group II: Epidural analgesia Levobupivacaine 0.2% @ 6ml/hr. Statistical evaluation: Hemodynamic profiles, Onset of analgesia, extent of sensory and motor block  were recorded.  To compare the change in a parameter at two different time intervals paired "t" test was used. Block characteristics were analysed using Mann Whitney U test.Results:Both Ropivacaine and levobupivacaine provided excellent analgesic effect, a good hemodynamic stability and complication free infusion. As compared to levobupivacaine, ropivacaine had an early motor block recovery, early achievement of VAS score 0, ability to achieve higher levels of block and finally prolongation of analgesic effect even after the infusion was stopped.Conclusion:As compared to levobupivacaine, ropivacaine seems to be a better option for continuous epidural infusion owing to early motor block recovery and prolonged analgesia   after the infusion was stopped.